Basalt pseudokarst development in the Lesotho Highlands, southern Africa. (20th February 2022) - Knight, Jasper; Grab, Stefan W.
Abstract: Subaerial physical, chemical and biological weathering processes are significant contributors to mountain landscape development worldwide, and over long time scales. This paper reports on pseudokarst features formed by different subaerial weathering processes on a high-elevation basalt plateau surface in the Maloti–Drakensberg mountains of eastern Lesotho, southern Africa. Different mesoscale landforms identified on this plateau surface include enclosed depressions (containing seasonal pools) that are morphologically similar to karstic solutional features. Such basalt pseudokarst landforms have not been previously described. This study uses field data on depression morphometry, sediments, water chemistry and rock surface hardness to explore the varied subaerial weathering and erosion processes contributing to pseudokarst depression development. Results show that physical, chemical and biological weathering and erosion processes in combination can impact on the basalt land surface in widening and deepening these depressions. An evolutionary model for pseudokarst depression development proposes that different weathering processes in combination within the 'critical zone' cause changes in depression morphology, and that there are significant feedbacks between bedrock, weathering, and the development of distinctive micromorphological forms. It is likely that similar pseudokarst landforms from other locations with non-carbonate substrates have been under-reported in the literature.